You can Be Anyone; but there are Limits: A Gendered Reading of Sexuality and Player Avatar Identification in Dragon Age : Inquisition - Hassan, Mohamed S. (Gamevironments, 2017)
Dragon Age: Inquisition's (2014) release opened a new world of character creation for the single-player RPG genre. Upon release, it allowed the player an extensive amount of customization. In addition to the typical variety of choices associated with hairstyle and color, face structure, tattoos, eye color, scarring, etc. the game also provides ingame unique sexuality quest lines that highlight the spectrum of sexual choices, race-defined features, different class options, and body-positive representations, which the player could project onto their avatar. However, in a game heralded asgroundbreaking for representation, the creators fail to acknowledge the non-binary gender expressions of their players, instead, forcing the player to choose between the traditional male and female characters. This paper seeks to explore the different ways in which Dragon Age: Inquisition (DAI) purports to incorporate modern notions of representation in the sphere of gender and sexuality but fail to do so, instead, reinforcing traditional binary representations of gender and sexuality informed by racial and religious assumptions.